2005
DOI: 10.1080/09637480500398835
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the antioxidant activity of roasted tea with green, oolong, and black teas

Abstract: Although the antioxidant properties of green, oolong, and black teas have been well studied, antioxidant activity has not been examined in roasted tea. Therefore, in the current studies, we investigated the antioxidant activity of roasted tea in comparison with those of green, oolong, and black teas. Using water extracts of the various teas, we examined the total phenolic content as well as the antioxidant activities, including the reducing power, the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 28 publications
5
37
0
2
Order By: Relevance
“…Embora os procedimentos encontrados na literatura sejam semelhantes (variando a massa de material seco de 1,0 a 1,5 g em um volume final de água de 100-250 mL), parece não haver uma forma padronizada para a preparação de amostra de chás para a análise 5,11,30,31 . Em todas as análises do presente trabalho as amostras de chá foram preparadas com o sachet fechado da mesma forma como aquela ingerida pelo consumidor e de maneira semelhante à efetuada em outro trabalho 30 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Embora os procedimentos encontrados na literatura sejam semelhantes (variando a massa de material seco de 1,0 a 1,5 g em um volume final de água de 100-250 mL), parece não haver uma forma padronizada para a preparação de amostra de chás para a análise 5,11,30,31 . Em todas as análises do presente trabalho as amostras de chá foram preparadas com o sachet fechado da mesma forma como aquela ingerida pelo consumidor e de maneira semelhante à efetuada em outro trabalho 30 .…”
Section: Resultsunclassified
“…Além disso, o processo para embalagem da ervas nos envelopes, incluindo a possível inclusão de excipientes nas formulações dos sachets, pode levar a uma alteração significativa da atividade antioxidante 31,36,37 .…”
Section: Capacidade Antioxidante Totalunclassified
“…Reducing powers and total polyphenols of tea extracts at 2, 8 and 18 h of extraction correlated significantly (R 2 = 0.98, 0.99 and 0.99, respectively). Satoh et al [27] also observed that there was a strong correlation between the RP and total phenolic content of different tea extracts including black tea. However, Psarra, et al [28] found a poor correlation (R 2 =0.60) between RP and total polyphenol of wines and also a high correlation (R 2 =0.81) for radical scavenging activity.…”
Section: Antioxidant Activitymentioning
confidence: 92%
“…(+)-Catechin and (-)-Epicatechin contents: Determination (+)-catechin and (-)-epicatechin in date seeds extracts was performed according to the method of Satoh [16]. In brief, high-performance liquid chromatography equipped with 125 binary HPLC pump, 2475fluorescence detector, 717 plus auto sampler and inline degasser AD was used (Waters Corporation, Milford, MA., USA).…”
Section: Antioxidant Propertiesmentioning
confidence: 99%